2022
DOI: 10.1186/s40168-022-01348-2
|View full text |Cite
|
Sign up to set email alerts
|

Chicken intestinal microbiota modulation of resistance to nephropathogenic infectious bronchitis virus infection through IFN-I

Abstract: Background Mammalian intestinal microbiomes are necessary for antagonizing systemic viral infections. However, very few studies have identified whether poultry commensal bacteria play a crucial role in protecting against systemic viral infections. Nephropathogenic infectious bronchitis virus (IBV) is a pathogenic coronavirus that causes high morbidity and multiorgan infection tropism in chickens. Results In this study, we used broad-spectrum oral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…It has also previously been observed that depletion of the microbiota leads to an impaired immune response to nephropathogenic IBV (76). In our study, large, genotype-independent differences in the composition of the microbiota were observed in IBV vaccinated vs. unvaccinated birds.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…It has also previously been observed that depletion of the microbiota leads to an impaired immune response to nephropathogenic IBV (76). In our study, large, genotype-independent differences in the composition of the microbiota were observed in IBV vaccinated vs. unvaccinated birds.…”
Section: Discussionmentioning
confidence: 86%
“…It is also possible that exposing chickens to different microbial sources early in life may lead to differences in the relationship between cDCs and the microbiota, as the gut microbiota plays an important role in shaping the chicken immune system (2), with early-life antibiotic exposure; exposure to adult caecal microbes and raising environment (cage vs. litter floor pens) all impacting the maturation of the chicken immune system (4,74,75). It has also previously been observed that depletion of the microbiota leads to an impaired immune response to nephropathogenic IBV (76). In our study, large, genotype-independent differences in the composition of the microbiota were observed in IBV vaccinated vs. unvaccinated birds.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have consistently indicated that the administration of levofloxacin can disturb the equilibrium of the intestinal microbiota, thereby inducing antibiotic-associated inflammation within the gastrointestinal tract [ 55 ]. Moreover, previous research conducted by our team and other scholars has provided evidence that the depletion of the intestinal microbiota resulting from the administration of antimicrobial drugs substantially elevates the likelihood of bacterial infectious diseases [ 53 , 54 , 72 74 ]. This correlation is closely linked to the reduction of immunoregulatory metabolites derived from the intestinal microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Till now, studies about the influence of intestinal microbiota on viral infection are mainly conducted in mammalian model. Recent work demonstrated that intestinal microbiota improved resistance of chicken against nephropathogenic infectious bronchitis virus ( 12 ), suggesting a conserved role of microbiota in regulating viral infection. However, the influence of commensal bacteria on viral infection in lower vertebrates is largely unknown.…”
Section: Introductionmentioning
confidence: 99%